2012
DOI: 10.2217/epi.12.46
|View full text |Cite
|
Sign up to set email alerts
|

Blood Chromatin as a Biosensor of the Epigenetic Milieu: A Tool for Studies in Living Psychiatric Patients

Abstract: This article constructs an argument for using blood chromatin (contained in nucleated blood cells) as a protein biosensor to integrate the ambient epigenetic influences in the internal milieu. An analogy is made to blood glycated hemoglobin (HbA1c) in diabetes as an integrated proxy for glucose levels and body-wide protein glycation. Genome-wide chromatin can serve as an organizing principle that bridges the central and peripheral compartments by entraining commensurable gene networks. Chromatin deposition alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…While postmortem investigations are able to serve as a useful snapshot at the time of death, the ability to measure and monitor histone marks over time as marker of disease progression, improvement, or as a predictor of pharmacological response are only possible using peripheral blood cells. A strong rationale for the use of blood chromatin ‘levels’ as a type of biosensor that registers the epigenetic milieu has been proposed elsewhere (Sharma 2012). Furthermore, previous studies have indicated the mRNA patterns of expression patterns in lymphocytes are capable of distinguishing between psychiatric diagnostic groups (Middleton et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…While postmortem investigations are able to serve as a useful snapshot at the time of death, the ability to measure and monitor histone marks over time as marker of disease progression, improvement, or as a predictor of pharmacological response are only possible using peripheral blood cells. A strong rationale for the use of blood chromatin ‘levels’ as a type of biosensor that registers the epigenetic milieu has been proposed elsewhere (Sharma 2012). Furthermore, previous studies have indicated the mRNA patterns of expression patterns in lymphocytes are capable of distinguishing between psychiatric diagnostic groups (Middleton et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMC) have been used as a proxy for central nervous system (CNS) tissue. PBMC are non-invasive to collect from living subjects and serve as surrogates for brain tissue molecular changes, though there can be limited coherence between PBMC and CNS biomarkers in various circumstances [47,48]. D'Addario et al 2012 examined antidepressant effects on BDNF DNA methylation using PBMC from forty-nine human subjects diagnosed with bipolar disorder type 1 (BD1), forty-five subjects with bipolar disorder type 2 (BD2), and fifty-two healthy controls (HC) [49].…”
Section: Bdnf (Brain-derived Neurotrophic Factor)mentioning
confidence: 99%
“…An ELISA kit was used to measure H3S10phos (Active Motif #53111) as well as Total H3 (#53110) from acid histone extracts of PBMC from human subjects (Sharma et al, 2006; Sharma, 2012; Chase et al, 2015). Samples were measured in duplicate using a 96-well format with multiple controls: 1) a standard curve; 2) plate-control (invariant sample); and 3) randomized and blinded plate position.…”
Section: Dear Editorsmentioning
confidence: 99%